2014
DOI: 10.1177/0040517514530027
|View full text |Cite
|
Sign up to set email alerts
|

A laser imaging method for machine vision detection of white contaminants in cotton

Abstract: The existing machine vision systems cannot efficiently detect white contaminants in cotton under the illumination of visible lights, because their color is the same or very close. To solve the problem, this article proposes an imaging method based on line lasers. Under the illumination of a line laser, the white contaminants and cotton showed the differences in the optical characteristic of their surface. Then, according to the features of the intensity of their reflected lights or the distribution of the fluf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The results indicated that it's still difficult to detect transparent plastic films although the contrast between object and background was increased effectively. Liu et al [9] used linear laser cross-sectional imaging to distinguish typical white contaminants from cotton. 12 types of white contaminants including semitransparent plastic mulch and white plastic film were used in their experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that it's still difficult to detect transparent plastic films although the contrast between object and background was increased effectively. Liu et al [9] used linear laser cross-sectional imaging to distinguish typical white contaminants from cotton. 12 types of white contaminants including semitransparent plastic mulch and white plastic film were used in their experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The availability and low commercial value of digital cameras and scanning devices have contributed to an increase in the number of analytical methodologies reported in the literature. [18][19][20] Mustac and Li 18 used î„„uorescence images in cotton samples with a digital single-lens reî„„ex camera (DSLR) to identify and classify thirteen types of residues present in cotton.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 20 proposed a method to distinguish white contaminants (paper, plastic and feathers) present in cotton with white tones by using red line laser images with a power of 50 MW and a wavelength of 650 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, the harvested cottons contain some degree of cotton plant-related contaminants and other irregular foreign matter [2,3]. During subsequent ginning and cleaning practices, great efforts have been made to remove these undesired contaminants as much as possible [4].…”
Section: Introductionmentioning
confidence: 99%